VD_FINDINFO HC / 2013 / 482 vom 7. Juni 2013 - VD Tribunal cantonal (2013)
JUSTE MOTIF, RÉSILIATION IMMÉDIATE, INDEMNITÉEN GÉNÉRAL, POUVOIR D'APPRÉCIATION, FARDEAU DE LA PREUVE | 4 CC, 8 CC, 337 al. 2 CO, 337 CO, 337c al. 3 CO, 337c CO, 308 CPC (CH), 310 CPC (CH), 312 al. 1 CPC (CH)